The Dialectics of TheoLogis and TheoLegis in the Meaning of Justice - Sunaryo, Sidik; Purnamawati, Shinta Ayu; Arifin, Ridwan (Faculty of Law, University of Muhammadiyah Malang, 2026)
This article examines the meaning of justice through the dialectical relationship between TheoLogis justice and TheoLegis justice as two epistemological horizons in shaping and enforcing law. The study seeks to clarify the interaction between transcendental moral values and comprehensive understanding of justice through legal reasoning within contemporary legal systems. TheoLogis justice is conceptualised as a value orientation grounded in divine revelation and moral theology, providing law with a transcendental ethical foundation. However, when detached from epistemic humility, TheoLogis justice may risk formalisation and authoritarian domination. By contrast, TheoLegis justice situates legal rationality, social experience, and human values as mediating instruments through which divine values are translated into rational, contextual, and publicly accountable legal norms. Using a legal philosophy and legal theology approach, this study demonstrates that justice does not emerge as a fixed or singular concept but as a dialectical process between text and context, between the universality of values and the plurality of social realities. Within the Indonesian context, TheoLegis synthesis acquires constitutional significance through Pancasila, which integrates divine values, humanity, and social justice without reducing law to either secular positivism or normative theocracy. The main contribution of this article is the formulation of the TheoLogis-TheoLegis framework as an alternative conceptual approach for interpreting justice in pluralistic legal systems. In this framework, TheoLegis justice functions as an epistemological bridge that translates transcendental values into rational legal reasoning, enabling law to operate not merely as a coercive instrument but as a form of practical wisdom oriented toward human dignity, social balance, and substantive justice.